Fully Vapor‐Deposited Heterostructured Light‐Emitting Diode Based on Organo‐Metal Halide Perovskite. (8th January 2016) - Genco, Armando; Mariano, Fabrizio; Carallo, Sonia; Guerra, Valentino L. P.; Gambino, Salvatore; Simeone, Daniela; Listorti, Andrea; Colella, Silvia; Gigli, Giuseppe; Mazzeo, Marco
Abstract : The first example of an efficient, fully vapor‐processed, perovskite‐based electroluminescent device is reported. This innovative heterostructured device represents an important advancement of the technology, allowing for complete manufacture without breaking the vacuum, thus for a better control of charge transport and electroluminescent properties of the device constituents.